Er skam en moralsk følelse? En sammenligning af individuel og gruppebaseret skam - Sánchez, Alba Montes (K&K - Kultur og Klasse, 2018)
Is shame a moral emotion? After the Muhammad cartoons controversy, many Danes argued that freedom of speech should be limited by a sense of decency, that insulting Islam for the sake of insult was shameful. Ten years later, the Danish government’s anti-refugee policy led some to say they were ashamed of being Danish. Here shame is given moral significance as the guardian of decency. However, psychologists like Tangney and Dearing have claimed that shame is morally counter-productive: it makes us react in antisocial ways, covering up our failings, shunning contact with others or lashing out in anger. Some have recently argued that the rise of right-wing populism in many Western nations is fueled by the psychological mechanism of transforming shame into rage. This seems a case of shame backfiring to cause antisocial behavior. In this paper, I seek to illuminate this dilemma by analyzing how self and others relate in shame. I defend that shame is an emotion of social self-consciousness, where one’s own self-assessment is fundamentally mediated by others. It may pull us in moral and immoral directions, but it is anyway part of the sensibilities that make us moral. My central examples, though, are cases of group-based shame. Is shame equally appropriate, and does it have the same significance, when it is group-based? I argue that the conditions of appropriateness change, but the structure of the emotion and its moral significance remains unchanged.